Matrix metalloproteinase-3 is a potent prognostic factor associated with cell proliferation and migration in prostate cancer - Ai Sato; Kiyoshi Takagi; Mio Yamaguchi-Tanaka; Jotaro Okushima; Yuto Yamazaki; Akihiro Ito; Takashi Suzuki (Experimental and Molecular Pathology)
Prostate cancer is a common malignancy in men around the world, and it is crucial to explore novel biomarkers to improve its treatment. Prostate cancer cells typically invade the surrounding stroma, and remodeling of the extracellular matrix (ECM) is a crucial step in the progress of prostate cancer. Matrix metalloproteinase-3 (MMP3) is an enzyme that degrades several ECM components and is implicated in human malignancies. However, the clinical and biological significance of MMP3 has not been well elucidated.We therefore immunolocalized MMP3 in prostate cancer tissues (n = 117) and demonstrated that MMP3 immunoreactivity was correlated with aggressive phenotype of prostate cancer, including higher proliferation/invasion ability, and shorter disease-free survival. In addition, subsequent in vitro analysis revealed that overexpression of MMP3 significantly increased the proliferative and migratory abilities of PC-3 and DU-145 prostate cancer cell lines, depending on conditioned media from WMPY-1 prostate stromal cells.It was concluded that MMP3 might contribute to prostate cancer progression by modifying the ECM surrounding prostate cancer cells and could serve as a potent prognostic factor in prostate cancer.